Evolution of dispersion-engineered metasurfaces: Debye relaxation and folded path concept - Hammad Ahmed; Buxiong Qi; Xianzhong Chen (Light: Science & Applications)
Abstract Dispersion engineering is advancing with recent breakthroughs in metasurfaces using the 2nd-order Debye relaxation and the folded-path concept, greatly improving relevant applications such as imaging, beam shaping, and cloaking.